Strengthening screening for infectious diseases and vaccination among migrants in Europe - ECDC ad hoc scientific panel (2021)
Funding Information: SH is funded by the National Institute for Health Research (NIHR Advanced Fellowship NIHR300072), the Academy of Medical Sciences (SBF005\1111), and the European Society for Clinical Microbiology and Infectious Diseases (ESCMID) through an ESCMID Study Group for Infections in Travellers and Migrants (ESGITM) research grant. MP is supported by the National Institute for Health Research (NIHR Post-Doctoral Fellowship, PDF-2015-08-102). The views expressed in this publication are those of the author(s) and not necessarily those of the NHS, the NIHR or the UK Department of Health. Funding Information: SH is funded by the National Institute for Health Research ( NIHR Advanced Fellowship NIHR300072 ), the Academy of Medical Sciences ( SBF005\1111 ), and the European Society for Clinical Microbiology and Infectious Diseases (ESCMID) through an ESCMID Study Group for Infections in Travellers and Migrants ( ESGITM ) research grant. MP is supported by the National Institute for Health Research ( NIHR Post-Doctoral Fellowship , PDF-2015-08-102 ). The views expressed in this publication are those of the author(s) and not necessarily those of the NHS, the NIHR or the UK Department of Health. Publisher Copyright: © 2020 The Authors